Climate-Tourism Information Scheme (CTIS) for sport events from past: analysis of cases of 1980 Summer Olympics (Moscow) and 2018 FIFA World Cup - Maratkanova, Varvara; Konstantinov, Pavel (Geographica Pannonica, 2023)
This article provides a quantitative analysis of local climate-related factors that may influence the organization of large sport events in Moscow, Russia, and its graphic representation in form of CTIS (Climate-Tourism Information Scheme) with decade resolution for 1991-2021. The individual CTIS for two historical sport events with daily resolution were also done, and then compared to meteorological data recorded during two large sport events to assess the agreement between averaged and actual conditions, which was found to be good enough for CTIS to serve as basic evaluation method. The CTIS-difference with sport events in Moscow compared with cases of Doha and Tokyo seem to be more about identifying the time period with biggest thermal comfort frequencies, instead of looking for occurrences of heat stress conditions. According to 1980 Summer Olympics and 2018 FIFA World Cup events it can be noted that time period was planned satisfactorily.